Analysis of Factors That Influence Continuance Use Intention of Mobile Banking Users Using Expectation Confirmation Model - Ginting, Rudi; Syarifuddin; Soeprapto, Adi; Akhirianto, Pas Mahyu; Widya Adnyani, Luh Putu (SEULANGA SYSTEM PUBLISHER, 2023)
This research aims to see the results of the level of measurement of continuity of use intention in mobile banking and what variables have an influence. This study uses a quantitative approach. In this research, data collection was carried out through a literature study, observation, and surveys. Researchers analyzed demographic data using Microsoft Excel. Researchers analyzed and interpreted the research results by describing demographic data, outer models, and inner models. The conclusion of the research results, namely this research has succeeded in measuring the level of continuance use intention (CUI) based on the coefficient of determination (R2), namely 0.7 (70%) categorized as medium-level sustainability intention, which is influenced by the variables used in the research model. The research results succeeded in determining the factors that influence continuance use intention (CUI), namely confirmation, perceived usefulness, satisfaction, and perceived security. The research results also succeeded in identifying factors that did not influence continuance use intention (CUI), namely self-efficacy, which received a value below the threshold for the path coefficient, namely 0.02, and a t-test value of 0.25, indicating that this relationship was rejected and had no significant effect.